Potential of Bajakah Tampala Root Extract (Spatholobus littoralis Hassk) as an Antibacterial Agent Against Vibrio harveyi - Kana Maulida; Iwan Sahrial Hamid; Maslichah Mafruchati; Bodhi Agustono; Amung Logam Saputro (Universitas Airlangga, 2026)
Antibiotics are commonly used to treat vibriosis in shrimp. However, their prolonged use at high doses may lead to the development of antibiotic resistance. As a preventive measure against antibiotic resistance, the use of natural antibacterial agents is required. Bajakah tampala root (Spatholobus littoralis Hassk) has been reported to possess antibacterial properties. This study employed six treatment groups: a positive control using a tetracycline antibiotic disc, a negative control using distilled water and CMC-Na, and four treatment groups (P1, P2, P3, and P4) treated with Bajakah tampala root extract (Spatholobus littoralis Hassk) at concentrations of 25%, 50%, 75%, and 100%, respectively. After treatment, the diameters of the inhibition zones were measured. The data obtained were analyzed using the Shapiro–Wilk normality test, followed by one-way analysis of variance (ANOVA). The results showed that treatment P4, with a 100% concentration of Bajakah tampala root extract (Spatholobus littoralis Hassk), produced an inhibition zone diameter comparable to that of the positive control.